Evaluasi Rasionalitas Penggunaan Obat ditinjau dari Indikator Peresepan World Health Organization (WHO) Pasien Rawat Jalan Poli Penyakit Dalam Periode Januari-Juni 2015 di Rumah Sakit Umum Bahteramas Provinsi Sulawesi Tenggara - Hamsidi, Rini; Fristiohady, Adryan; Musabar, Nasyrah (Pharmauho: Jurnal Farmasi, Sains, dan Kesehatan, 2015)
On 1993, prescribing in Indonesia was still irrational. It can be seen from many pharmacy (3,5/patient), overuse of antibiotics (43%), and inappropriate overuse of injections (10-80%). This study aimed to evaluate rationality of drugs use based on prescribing indicators by WHO of outpatient in poly interna medicine at Bahteramas general hospital of Southeast Sulawesi from January to June period of 2015 and analyze significant differences of each month. Method of this study was retrospective and concurrent. Total amount of sample were 600 recipes. Technic of sampling was simple randomized sampling. Results of the study compared with WHO standards on 1993. Analyze significant differences of each month of this study was SPSS 16.0 with Kruskal Wallis method. Results of this study showed that average drug prescribed was 3; average percentage of medicines prescribed by generic name was 85.39%; average percentage encounters with antibiotic prescribed was 36%; average percentage encounters with injection prescribed 0%; and average percentage of medicines prescribed from Formulary of Hospital 99.81%. Result show that drug use at Bahteramas general hospitals each monthof outpatient poly interna period January-June 2015 there was no difference (p â‰¥ 0.05)Keywords: rational, Â interna, Bahteramas, recipes, WHO